Mass exchange dynamics during the second filtration drying period - Atamanyuk, Volodymyr; Gumnytskyi, Yaroslav (Publishing House of Lviv Polytechnic National University, 2009)
The work is dedicated to theoretical and experimental investigations of kinetics and dynamics of filtration drying of capillary and porematerials, andmineral granulated fertilizers, in particular. The proposed physical model of a moist particle and the differential system of equations which describes heat exchange in the second drying period enables to determine the transfer velocity ofmass-exchange zone in a dispersion layer of thematerial during filtration drying. Стаття призначена експериментальним і теоретичним дослідженням кінетики і динаміки фільтраційного висушування дисперсних капілярно-пористих матеріалів., зокрема, мінеральних гранульованих добрив. Запропонована фізична модель вологої частинки та система диференційних рівнянь, що описує тепломасообмін у другому періоді висушування і дає змогу визначити швидкість переміщення зони масообміну в шарі дисперсного матеріалу під час фільтраційного висушування.
Динаміка масообміну під час другого періоду фільтраційного висушування
Keywords: kinetics; dynamics; filtration drying; dispersionmaterial; fertilizers; second period; physical model; mathematical model; кінетика; динаміка; фільтраційне висушування; дисперсний матеріал; мінеральні добрива; другий період; математична модель; фізична модель